Oceans for Prosperity : Reforms for a Blue Economy in Indonesia - World Bank (World Bank, Washington, DC, 2021)
Oceans are vital for Indonesia’s economy and social welfare. However, there are challenges to the extent and integrity of Indonesia’s marine and coastal ecosystems that, if not managed well, could undermine the potential of Indonesia’s ocean economy. Compounding these long-term challenges are more immediate pressures from the COVID-19 pandemic. Both long and short-term challenges can be addressed through a blue economy strategy; such a strategy is being pursued by the Government of Indonesia through a range of initiatives. Developing a blue economy will require substantial investments and policy reform that build on these initiatives.